Extracellular cold-inducible RNA-binding protein in renal ischemia–reperfusion injury and its progression to chronic kidney disease - Max Brenner; Ping Wang (Molecular Medicine, 2026)
Abstract Acute kidney injury (AKI) from renal ischemia–reperfusion (IR) injury is a major cause of acute organ dysfunction with significant morbidity and mortality. Critically, up to 50% of AKI survivors progress to chronic kidney disease (CKD), yet the mechanisms driving this maladaptive transition remain incompletely understood, and effective therapies are lacking. Work from our group and others has now identified extracellular cold-inducible RNA-binding protein (eCIRP), a damage-associated molecular pattern, as a mediator of acute kidney injury and its progression to CKD. This review synthesizes current knowledge regarding eCIRP's pathobiological role in renal IR injury, its mechanisms of action across multiple cell types and signaling pathways, and its possible involvement in the AKI-to-CKD transition. We discuss how eCIRP activates pattern recognition and cytokine receptors (particularly TLR4, TREM-1, and IL-6Rα) on endothelial cells, monocytes/macrophages, and tubular epithelial cells to promote inflammation, oxidative stress, ferroptosis, and dysregulated cell death pathways. Additionally, we examine emerging evidence that eCIRP perpetuates maladaptive repair and fibrosis through epithelial-to-mesenchymal transition, PANoptosis-driven tissue damage, and TGF-β/Smad3-dependent fibroblast activation. Finally, we review eCIRP-targeting therapeutic strategies including anti-CIRP antibodies, peptide inhibitors (C23, M3, MOP3), and miRNA mimics, which show promising preclinical efficacy in reducing kidney injury and attenuating fibrotic changes associated with CKD development. These findings open new avenues for intervention at multiple stages of kidney disease and may ultimately improve long-term outcomes in patients with renal IR injury.